Mental health problems and their impacts in the workplace: A systematic review - Tran, Thi Ai Vy; Tran, Thi Thu Hien; Ton, Nguyen Trong Hien (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Nowadays, there is increasing recognition of workplace mental health (MH) issues as a significant problem in many countries, which negatively impacts both spiritual and economic burdens on employees and employers. This growing concern has attracted more research interest in how to manage it. In this context, this report aims to identify the impacts, damages, relevant factors, and consistent solutions that may help employees manage situations effectively and support business organizations in reducing lost productivity through information and suggestions. The methods employed involve reviewing academic articles, newspapers, and statistical data from several scholars in different countries to seek the essential correlation between workplace components and MH problems. This approach highlights the practical approaches of relevant parties to ensure healthier workplace priorities and improved quality of life for employees. Implementing comprehensive psychological health programs in the workplace is critical for supporting employee well-being and organizations’ productivity. This report also provides recommendations for practical implications and contributes to the growing body of MH research.